2012
DOI: 10.1177/1049731512450074
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Chinese Virtues Questionnaire

Abstract: Objectives: The present study examined the factorial invariance and functional equivalence of the Values in Action Inventory of Strengths (VIA-IS) among the Chinese. Methods: A total of 839 undergraduate students completed the 240-item Simplified Chinese version of the VIA-IS online. Another 40 students participated in qualitative interviews to examine the meaning and function of the items in Chinese culture. Results: A total of 144 items were removed from the original version questionnaire (240-item) because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 29 publications
11
110
1
7
Order By: Relevance
“…Vandenberg and Lance (2000) propose that establishing the measurement equivalence or measurement invariance primarily is required to guarantee similar latent constructs across groups so that meaningful comparisons can be performed. It should be noted that, although different scholars adopted different labels to name their factors (Duan et al 2012;Ho et al 2016;McGrath 2015), the three dimensions of strengths are essentially the same. Temperance strength reflects "an intrapersonal strength that describes people who persist in achieving goals and exhibit self-control", which reflects the individual orientation of strengths that are consistent with conscientiousness (Duan et al 2012) and self-control (McGrath 2015); intellectual strength means "the curiosity and zest for creativity of an individual" that are reflected by vitality (Duan et al 2012) and inquisitiveness (McGrath 2015); and interpersonal strengths reflects "the love, concern, and gratitude of a person toward others", which is consistent with the relationship of Duan et al (2012) and caring of McGrath (2015).…”
Section: Relationship Between Demographic Variables and Strengthsmentioning
confidence: 95%
See 2 more Smart Citations
“…Vandenberg and Lance (2000) propose that establishing the measurement equivalence or measurement invariance primarily is required to guarantee similar latent constructs across groups so that meaningful comparisons can be performed. It should be noted that, although different scholars adopted different labels to name their factors (Duan et al 2012;Ho et al 2016;McGrath 2015), the three dimensions of strengths are essentially the same. Temperance strength reflects "an intrapersonal strength that describes people who persist in achieving goals and exhibit self-control", which reflects the individual orientation of strengths that are consistent with conscientiousness (Duan et al 2012) and self-control (McGrath 2015); intellectual strength means "the curiosity and zest for creativity of an individual" that are reflected by vitality (Duan et al 2012) and inquisitiveness (McGrath 2015); and interpersonal strengths reflects "the love, concern, and gratitude of a person toward others", which is consistent with the relationship of Duan et al (2012) and caring of McGrath (2015).…”
Section: Relationship Between Demographic Variables and Strengthsmentioning
confidence: 95%
“…the issue of variant factor structures of the VIA inventory in different cultures and countries (Ho et al 2014a, b), including two-to five-factor models in 14 different studies (Azañedo et al 2014;Brdar and Kashdan 2010;Khumalo et al 2008;Macdonald et al 2008;Park and Peterson 2010;Peterson and Park 2004;Peterson and Seligman 2004;Ruch et al 2010;Shryack et al 2010;Singh and Choubisa 2010). Recently, Duan et al (2012) adopted the combined emic-etic approach to select items with functional equivalence and conceptual equivalence in the quantitative and qualitative analyses, which resulted in a three-dimensional strengths model (i.e., relationship, vitality, and conscientiousness). The follow-up studies have demonstrated sound psychometric properties of the revised questionnaire (Duan et al 2013;Zhang et al 2014).…”
Section: Relationship Between Demographic Variables and Strengthsmentioning
confidence: 97%
See 1 more Smart Citation
“…Shryack et al (2010) tested several different models and concluded that the threefactor model was most reliable in a sample of twins from Minnesota administered the VIA-IS. In two studies administering the Chinese Virtues Questionnaire, a variant of the VIA-IS developed specifically for use in mainland China, a three-factor structure emerged labeled interpersonal, which is consistent with Caring; vitality, which closely parallels the Inquisitiveness component; and cautiousness, which is consistent with Self-Control (Duan, Ho, Bai, & Tang, 2013;Duan et al, 2012). In every study included in this article as well as in the work by Shryack et al and Duan et al, the Caring component Notes: The x-y notation indicates the number of components retained and the location of the component within that solution.…”
Section: Consistent Findingsmentioning
confidence: 97%
“…26,27 Sample items include "I am a person who is full of gratitude" (relationship), "I am a true life-long learner" (vitality), and "I will control my emotions" (conscientiousness). The respondents were asked to rate the extent to which each item could describe them on a 5-point Likert scale, ranging from 1 (very much unlike me) to 5 (very much like me).…”
Section: Chinese Virtues Questionnaire (Cvq)mentioning
confidence: 99%